East Germany's Angela Davis - Ross T Parks (Vernacular: New Connections in Language, Literature, & Culture, 2021)
Angela Davis is arguably the most famous member of the Black Panther movement. She reached prominence within the United States as a political dissident, educator, activist, and prisoner in the early 1970s. However, the United States government was not the only one with an eye on Davis. The Black Panther movement is well-known within the United States, with a complicated reputation among the public. Often framed as far-left radicals, the group and many of its members were heavily targeted by the FBI throughout its existence. The movement’s efforts are often categorized as the most extreme example of the Civil Rights movement within the United States as the late 1960s and 1970s gave way to social unrest, political assassinations, and the heightening of the Cold War. However, the group’s reach extends far beyond the borders of its country of origin. In fact, the work of the organization was of great interest to many people and governments abroad. The general understanding of the Black Panther movement is often lacking a global perspective, which is key to understanding its purpose and function. Many government officials and people, in particular behind the ‘iron curtain’, were drawn to and inspired by Davis’ activism. The case was perhaps most profound for the East German state during and soon after her imprisonment in the early 1970s. What first followed was a seemingly organic outpouring of support and solidarity for Davis in the East German media. However, to what extent this wave of support was indeed organic or orchestrated by a heavily regulated state-run media, remains unearthed. This paper will discuss when, why, and how the East German government viewed, used, and promoted the most prominent figure of the Black Panther Movement to further its own domestic political agenda.
Keywords: East Germany; Black Panthers; Media; GDR